The potential effectiveness of community health and nutrition volunteers on mothers' infant and young children feeding knowledge and practice in remote areas, Hajjah, Yemen - Abdulkareem Ali Hussein Nassar; Ahmed Al-Haddad (BMC, 2024)
Abstract Background The Infant and young child feeding (IYCF) practices directly affect the health, development and nutritional status of children under two years of age. However, IYCF counseling is one of the Community Health and Nutrition Volunteers (CHNVs) activities provided, which may contribute to improving the IYCF knowledge and practice among mothers. Since establishment of the CHNVs program in Yemen, its outcome has never been evaluated. Therefore, the aim of this study was to evaluate the role of CHNVs in improving the IYCF knowledge and practice among mothers in Hajjah governorate. Methods A comparative cross-sectional study design was conducted in Bani Qais and Al-Maghrabah districts, Hajjah governorate between January and April 2023. A three-stage cluster sampling method was used to select districts, volunteer villages and households. A total of 926 mothers were interviewed. A pre-tested structured questionnaire was used to collect data. SPSS 26 was used for data analysis. The multinomial logistic regression and Chi-Square test were used to compare the IYCF knowledge and practices among mothers between the volunteer and non-volunteer villages. Odds Ratio (OR) with 95% Confidence Interval (CI) were calculated. A p-value < 0.05 was considered statistically significant. Results The mothers in volunteer villages had significantly better breastfeeding and complementary feeding (CF) knowledge than mothers in non-volunteer villages. The OR of having good and moderate knowledge of breastfeeding were 3.5 (95%CI: 2.4-5.2) and 1.6 (95% CI: 1.2-2.2), respectively. The OR for good and moderate knowledge of CF were 1.7 (95% CI: 1.1-2.7) and 2.2 (95% CI: 1.5-3.0), respectively. Moreover, there is a statistically significant association in prevalence of Exclusively breastfed for the first two days after birth (EBF2D), Mixed milk feeding under six months (MixMF) and Bottle feeding 0-23 months (BoF) between volunteer and non-volunteer villages [(OR = 1.4, 95% CI: 1.0-1.8), (OR = 0.4, 95% CI: 0.2-0.8) and (OR = 0.5, 95% CI: 0.4-0.7), respectively]. Conclusions The study found that CHNVs play a significant effect in improving the breastfeeding and CF knowledge, and prevalence of EBF2D, MixMF and BoF practices among mothers in their villages compared to non-volunteer villages. Future follow-up study and expansion to other settings in different governorates is recommended.